Homogeneity of Severe Posttraumatic Stress Disorder Symptom Profiles in Children and Adolescents Across Gender, Age, and Traumatic Experiences Related to 9/11. Issue 5 (11th October 2016) - Guffanti, Guia; Geronazzo‐Alman, Lupo; Fan, Bin; Duarte, Cristiane S.; Musa, George J.; Hoven, Christina W.
Abstract: Patients with a posttraumatic stress disorder (PTSD) diagnosis according to the Diagnostic and Statistical Manual of Mental Disorders (4th ed., DSM‐IV ; American Psychiatric Association, 1994) will very likely not share all of the same symptoms, a consequence of the polythetic approach used in the DSM . We examined heterogeneity in the latent structure of PTSD symptoms using data from a previously published sample of 8, 236 youth a subset of which had been exposed to the September 11, 2001 attacks ( N = 6, 670; Hoven et al., 2005). Latent class analysis was applied (a) to PTSD symptoms alone, (b) to symptoms in combination with impairment indicators, and (c) to PTSD symptoms when stratified by age and gender, as well as by empirically defined classes of exposure. We identified 4 symptom classes: no disturbance (49.4%), intermediate disturbance (2 classes; 21.5% and 18.6%, respectively), and severe disturbance (10.5%). These classes varied not only in the severity of symptoms, but also in the configuration of symptoms. We observed a high probability of endorsing both PTSD symptoms and indicators of impairment only in the severe disturbance class. A similar 4‐class structure was found when the data were stratified by age, gender, and exposure classes. There were no significant differences as a function of age, gender, or exposure in the presence of severe PTSD. Heterogeneity was observed at intermediate levels of PTSD symptom severity. The specific PTSD symptoms that defined the severe PTSD profile could constitute the pathogenic aspects of a largely invariant and clinically meaningful PTSD syndrome.